Vanishing Financial Contagion? - Didier, Tatiana; Mauro, Paolo; Schmukler, Sergio L. (2012)
While a number of crises in emerging markets generated widespread contagion in financial markets during the 1990s, more recent crises (notably, in Argentina) have been mostly contained within national borders. This has led some observers to wonder whether contagion might have become a feature of the past, with financial markets now better discriminating between emerging countries with good and bad fundamentals. Available data suggest that the main channels that contribute to transmitting financial crises across countries are--if anything--even stronger today than in the 1990s. Moreover, anticipation by international investors may help to explain the near-absence of contagion in the context of the Argentine crisis. This paper argues that a prudent working assumption is that financial contagion has not vanished.